2008
DOI: 10.1002/app.28498
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mark–Houwink parameters of ethylene–norbornene copolymers and molecular characteristics estimation

Abstract: Ethylene-norbornene copolymers (ENC) with $ 50%, $ 25% and $ 15% norbornene (NB) fraction in a wide range of molecular weight were produced by metallocene catalysts. By coupling the gel permeation chromatography (GPC) with the intrinsic viscosity data in 1,2,4-trichlorobenzene (TCB)at 1508C, the Mark-Houwink parameters of ENC were determined and compared with previous classical analysis using polyethylene's relative parameters. The results indicated that parameter K was considerably increased with decreasing N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The preparation of the E-NB copolymer and E-NB-P terpolymer samples used in this work had been reported in literature. [21][22][23][24] The composition, molecular weight, and PDI data were cited from the sources.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of the E-NB copolymer and E-NB-P terpolymer samples used in this work had been reported in literature. [21][22][23][24] The composition, molecular weight, and PDI data were cited from the sources.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 summarized G e and M e of comb-like polymers. Different from other reported comb-like polymers that have a very low G e and show a several dozen times increase in M e , 25 it was found that the reduced M e (∼3.5 × 10 4 g/mol and ∼4.6 × 10 4 g/mol) of two weakly phase-separated samples is only several times larger than that of the corresponding linear polymer chains (∼17400 g/mol), 42 and the strongly phaseseparated sample has a M e (∼1.7 × 10 4 g/mol) comparable to that of linear polymer chains. Table 1 also shows that M e of other comb-like polymers is comparable to or larger than that of linear polymer chains.…”
Section: Influence Of Structure Parameters On Linear Rheological Beha...mentioning
confidence: 99%
“…The method of Ruchatz and Fink was adopted for the chemical shift assignments and copolymer composition estimates: 3 mol %Norbornene The molecular weight and molecular weight distribution were measured at 1508C in 1,2,4-trichlorobenzene using a Waters GPCV 2000 with a combined refractive index and viscosity detector. 35 …”
Section: Characterization and Measurementsmentioning
confidence: 99%